2021
DOI: 10.3390/fishes6030032
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial and Antibiofilm Activity of S-(-)-Limonene and R-(+)-Limonene against Fish Bacteria

Abstract: Brazilian fish farming goes together with the emergence of numerous bacterial diseases, with Aeromonas hydrophila being the main bacterial pathogen. As a consequence, antimicrobials are excessively used. Considering that antimicrobials are relatively stable and nonbiodegradable, medicinal plants and their phytochemicals have been used as alternative treatments of bacteriosis in fish farming. Limonene is a monoterpene available in two enantiomers: R-(+)-limonene and S-(-)-limonene. This study analyzed the antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
1
5
0
Order By: Relevance
“…Besides the antibacterial capability, Silva et al (2021) found that tambaqui (C. macropomum) fed with carvacrol had higher monocyte and neutrophil counts, phagocytic activity, and a higher survival rate when exposed to A. hydrophila infection [56]. Thus, we inferred that carvacrol could enhance the non-specific cellular immune function of grass carp and improve their ability to resist bacterial invasion Essential oils are commonly considered to have multi-target inhibitory effects on pathogenic bacteria and, in combination with conventional antibiotics, may enhance the activity, avoid the emergence of antibiotic resistance, and reduce drug use [59,60]. Pirog et al (2019) found that essential oils combined with other antimicrobials could destroy yeast and bacterial biofilm, thereby significantly decreasing their MIC [61].…”
Section: Discussionmentioning
confidence: 99%
“…Besides the antibacterial capability, Silva et al (2021) found that tambaqui (C. macropomum) fed with carvacrol had higher monocyte and neutrophil counts, phagocytic activity, and a higher survival rate when exposed to A. hydrophila infection [56]. Thus, we inferred that carvacrol could enhance the non-specific cellular immune function of grass carp and improve their ability to resist bacterial invasion Essential oils are commonly considered to have multi-target inhibitory effects on pathogenic bacteria and, in combination with conventional antibiotics, may enhance the activity, avoid the emergence of antibiotic resistance, and reduce drug use [59,60]. Pirog et al (2019) found that essential oils combined with other antimicrobials could destroy yeast and bacterial biofilm, thereby significantly decreasing their MIC [61].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of phytochemicals and antibiotics can cause antagonistic antimicrobial effects. For instance, Silva et al 326 combined two isoforms of limonene (Fig. 2 AZ ), ( S -(−)-limonene and R -(+)-limonene), and with oxytetracycline to apply against biofilms of A. hydrophila.…”
Section: Insights On the Combinatorial Effect And Interactions: Phyto...mentioning
confidence: 99%
“…It is classified as "generally recognized as safe" (GRAS) by the U.S. Food and Drug Administration and is widely used in the food and cosmetic industries [13]. Additionally, D-limonene also has analgesic, anti-inflammatory [17,18], antioxidant [19], neuroprotective [20], and antimicrobial [21] effects and has hence received extensive attention from researchers.…”
Section: Introductionmentioning
confidence: 99%